Reaching for the moon : the Cold War space race - Choi, John, 1970-; McGowen, Tom (Movements and moments that changed America., 2021)
Presents the history of the development of the space program during the Cold War, and highlights the importance of the space race to American history. Profiles famous astronauts and Project Apollo, and examines the impact of successes and failures during this period on future space exploration. Includes photographs and sidebars.